Invasive pneumococcal disease leads to activation and hyperreactivity of platelets. Issue 144 (August 2016) - Tunjungputri, Rahajeng N.; de Jonge, Marien I.; de Greeff, Astrid; van Selm, Saskia; Buys, Herma; Harders-Westerveen, Jose F.; Stockhofe-Zurwieden, Norbert; Urbanus, Rolf T.; de Groot, Phillip G.; Smith, Hilde E.; van der Ven, Andre J.; de Mast, Quirijn
Abstract: Using a novel porcine model of intravenous Streptococcus pneumoniae infection, we showed that invasive pneumococcal infections induce marked platelet activation and hyperreactivity. This may contribute to the vascular complications seen in pneumococcal infection.